2019
DOI: 10.1001/jamanetworkopen.2019.8325
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Physician Coprescribing of Opioids and Benzodiazepines After the Release of the Centers for Disease Control and Prevention Guidelines in 2016

Abstract: Key Points Question Was the release of the Centers for Disease Control and Prevention’s 2016 opioid prescribing guidelines associated with changes in the rate of coprescription of opioids and benzodiazepines? Findings This cohort study of administrative data for 4 897 464 patients found small, statistically significant decreases in the rate of coprescription in the 2 years after the guideline release. These decreases were seen only in the targeted guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 37 publications
(44 reference statements)
2
68
0
Order By: Relevance
“…Only one other study was found that reported an 11.1% rate of opioid prescribing using 2016 data from primary care clinics in a Virginia PBRN ( Tong et al, 2019 ). The 52.1% rate of potential concurrent opioid-sedative prescription was also high compared to the recently published national figures of 23.0% for a commercially insured population and 25.7% for the Medicare Advantage population ( Jeffery et al, 2019 ). The notably higher rates of opioid prescribing among elders are consistent with prior reports ( Paulozzi, Strickler, Kreiner, & Koris, 2015 ).…”
Section: Discussionmentioning
confidence: 67%
“…Only one other study was found that reported an 11.1% rate of opioid prescribing using 2016 data from primary care clinics in a Virginia PBRN ( Tong et al, 2019 ). The 52.1% rate of potential concurrent opioid-sedative prescription was also high compared to the recently published national figures of 23.0% for a commercially insured population and 25.7% for the Medicare Advantage population ( Jeffery et al, 2019 ). The notably higher rates of opioid prescribing among elders are consistent with prior reports ( Paulozzi, Strickler, Kreiner, & Koris, 2015 ).…”
Section: Discussionmentioning
confidence: 67%
“…The overall number of consult requests decreased over time, similar to trends seen within the VA and in the community demonstrating overall reductions in prescribing of concurrent opioids and benzodiazepines. [22][23][24] A few strategies have been previously described with mixed results for efficacy in reducing concurrent use, including EMR review of current co-prescribed patients with individualized and/or standardized recommendations to prescribers, an electronic EMR alert at the time of prescription entry with information on risks and/or recommended provision of naloxone, and an electronic consult evaluated by CPS prior to prescribing new concurrent treatment. [11][12][13][14][15] This intervention at the SFVAHCS provides further evidence supporting electronic consult interventions as one strategy to reduce new concurrent treatment with opioids and benzodiazepines and may be useful in integrated health care systems that have not yet addressed new concurrent use and/or when reductions in co-prescribing have plateaued.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Furthermore, a retrospective cohort study which used insurance claims from a U.S. national database of medical and pharmacy claims demonstrated significant reductions in opioid and benzodiazepine coprescribing within the 2 years after publication of the Centers for Disease Control and Prevention guidelines in 2016, which recommended avoiding the combination. 24 Thus, providers within the SFVAHCS may have already received information about the risks of concurrent Consults were most commonly placed by primary care and mental health providers. This is likely because these are front line care services where patients typically access treatment for musculoskeletal pain, anxiety, and insomnia, the same common treatment indications identified in the retrospective review by Pardo et al 15 The highest number of consults were placed by providers at the main medical center, where there are multiple primary care and mental health clinics.…”
Section: Deceased Veteransmentioning
confidence: 99%
“…Deidentified administrative claims data from OptumLabs Data Warehouse include medical and pharmacy claims, laboratory results, and enrollment records for >88 million privately insured individuals during the study period. The database contains enrollees with a diverse mixture of ages and ethnicities across all 50 states in the United States 5 and has been used to evaluate health care expenditures and usage in oncology populations 6‐9 . The institutional review board of the University of Alabama at Birmingham approved our study.…”
Section: Methodsmentioning
confidence: 99%
“…The database contains enrollees with a diverse mixture of ages and ethnicities across all 50 states in the United States 5 and has been used to evaluate health care expenditures and usage in oncology populations. [6][7][8][9] The institutional review board of the University of Alabama at Birmingham approved our study.…”
Section: Data Sourcementioning
confidence: 99%